Autonomous energy supply based on the wind-energy complex and hydrogen energy storage - S. I. Nefedkin; A. O. Barsukov; M. I. Mozgova; M. S. Shichkov; M. A. Klimova; С. И. Нефедкин; А. О. Барсуков; М. И. Мозгова; М. С. Шичков; М. А. Климова (Alternative Energy and Ecology (ISJAEE), 2019)
The paper proposes an alternative scheme of guaranteed electricity and heat supply of an energy-insulated facility with a high potential of wind energy without the use of imported or local fuel. The scheme represents a wind power complex containing the park of wind generators located at the points with high wind potential. The wind generators provide guaranteed power supply even in periods of weak wind. For heat supply of the consumer, all surplus of the electric power goes on thermoelectric heating of water in tanks of accumulators, and also on receiving hydrogen by a method of electrolysis of water. The current heat supply is carried out with the use of hot water storage tanks, and the heat supply during the heat shortage is carried out by burning the stored hydrogen in condensing hydrogen boilers. We have developed the algorithm of calculation and the program "Wind in energy" which allows calculating annual balance of energy and picking up necessary quantity of the equipment for implementation of the scheme proceeding from the annual schedule of thermal and electric loading, and also potential of wind energy in the chosen region. The calculation-substantiation of the scheme proposed in relation to the real energy-insulated object Ust-Kamchatsk (Kamchatka) is carried out. The equipment for the implementation of an alternative energy supply scheme without the use of imported fuel is selected and compared with the traditional energy supply scheme based on a diesel power plant and a boiler house operating on imported fuel. With the introduction of an alternative power supply scheme, the equipment of the traditional scheme that has exhausted its resource can be used for backup power supply. Using climate databases, a number of energy-insulated facilities in the North and East of Russia with high wind energy potential are considered and the conditions for the successful implementation of the energy supply scheme are analyzed. This requires not only a high average annual wind speed, but also a minimum number of days ...